2011
DOI: 10.1038/hr.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurements within the JNC7 pre-hypertensive range after 32 weeks of gestation are a risk factor for decreased fetal growth

Abstract: CORRESPONDENCEBlood pressure measurements within the JNC7 pre-hypertensive range after 32 weeks of gestation are a risk factor for decreased fetal growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…29 However, emerging evidence suggests that elevated BP among pregnant women without HDP is associated with increased risk of poor offspring health outcomes including fetal growth restriction and preterm delivery. [32][33][34][35] Our study extends these findings to an adverse maternal health outcome in later life.…”
Section: Discussionsupporting
confidence: 71%
“…29 However, emerging evidence suggests that elevated BP among pregnant women without HDP is associated with increased risk of poor offspring health outcomes including fetal growth restriction and preterm delivery. [32][33][34][35] Our study extends these findings to an adverse maternal health outcome in later life.…”
Section: Discussionsupporting
confidence: 71%
“…We are only aware of 2 earlier studies on the effect of level of blood pressure in nonhypertensive pregnancies on fetal growth, 6,9 and both studies report results in accordance with ours. One small Japanese study found that women with prehypertension at 32 gestational weeks had a slightly increased risk of SGA birth (odds ratio 1.09; 95% CI 1.01-1.17) compared with normotensive women.…”
Section: Comparisons To Earlier Studiessupporting
confidence: 76%
“…One small Japanese study found that women with prehypertension at 32 gestational weeks had a slightly increased risk of SGA birth (odds ratio 1.09; 95% CI 1.01-1.17) compared with normotensive women. 6 The study only included 71 women with prehypertension, and adjustments were solely made for maternal BMI. The second study reports the highest birth weights in pregnancies where the highest recorded DBP during pregnancy was 80 mm Hg (at higher blood pressure levels, the birth weights decreased).…”
Section: Comparisons To Earlier Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For nonpregnant adults, the risk of cardio vascular disease increases linearly as BP increases, even within the normo tensive range (Vasan et al 2001;Williams et al 2008). A few studies have examined BP as a continuous measure and found that higher BP, even within the normotensive range, also may impact birth weight and intra uterine growth restriction (Churchill et al 1997;Fukushima et al 2012). It is possible that elevated BP, albeit within the clinically normal range, alters uterine and placental perfusion, and impacts fetal growth.…”
Section: Discussionmentioning
confidence: 99%